Durability performance of lightweight aggregate concrete for housing construction - Zulkarnain, Fahrizal; Ramli, Mahyuddin (2008)

(untitled)
Durability can be defined as the ability of material to withstand the effects of its environment. In the building material its may be interpreted as chemical attack, water absorption and carbonation. Chemical attack usually encountered as aggressive groundwater, particularly sulphate, polluted air and spillage of reactive liquids. A chemical aspect of durability is the stability of the material itself, particularly in the presence of moisture. Concrete made with lightweight aggregate exhibit a higher moisture movement than is the case with normal weight concrete. Based on the a 24 hr absorption test, lightweight aggregate generally absorbs from 5 to 20 percent by weight of dry aggregate, depending on the pore structure of the aggregate. The important difference is that the moisture content in lightweight aggregates is largely absorbed into the interior of the particles whereas in normal weight aggregates it is largely surface moisture. Rate of absorption in lightweight aggregates is a factor which also has a bearing on mix proportioning, handling, and control of concrete, and depends on the aggregate particle surface pore characteristics plus other factors.